Parental food neophobia, feeding practices, and preschooler's food neophobia: A cross-sectional study in China. (1st June 2023) - Yong, Cuiting; Kuang, Xiaoni; Liu, Yan; Xiang, Caihong; Xi, Yue; Huo, Jiaqi; Liang, Jiajing; Zou, Hanshaung; Lin, Qian
Abstract: This study explores the relationship between parental food neophobia, feeding practices, and preschoolers' food neophobia in China. Methods: A cross-sectional study was conducted among 1616 pairs of preschoolers and their parents. Electronic questionnaires were conducted to collect information about social and demographic characteristics, scores of food neophobia among both children and their parents, parents' feeding patterns and children's dietary quality. Results: Children's average food neophobia score was 23.73 ± 4.45. There was a positive correlation between parental food neophobia score (β: 0.154; 95%CI: 0.113, 0.195), pressure to eat (β: 0.694; 95%CI: 0.423, 0.964), postpartum breastfeeding initiation (β: 0.010; 95%CI: 0.002, 0.018), and children's score of food neophobia. However, parental modeling (β: -0.470; 95%CI: -0.732, −0.207) and the frequency of children eating with their families at home (β: -0.407; 95%CI: -0.707, −0.108) were negatively associated with children's food neophobia scores. The consumption frequencies of vegetables (P < 0.001), fruits (P < 0.001), domestic animals and poultry (P < 0.01), aquatic products (P < 0.05), beans and their products (P < 0.01), eggs (P < 0.05) and nuts (P < 0.05) and children's dietary diversity score (P < 0.001) are negatively associated with children' food neophobia score. While the consumption frequencies of fast food (P < 0.001), sweets (P < 0.01) and puffed/fried food (P < 0.001) were positively associated with children's food neophobia. Conclusion: Chinese preschoolers' food neophobia needs more attention because children with high food neophobia tend to have lower dietary quality. Children whose parents have high-level food neophobia should be the focus of early prevention. Earlier postpartum breastfeeding, more use of parental modelling, less pressure to eat and higher frequency of children eating with families are helpful to reduce the incidence of children's food neophobia.